Perbandingan Gaya Bahasa Pada Puisi ‘Aku Mencintaimu Dalam Diam’ Karya Jalaluddin Rumi Dengan Puisi ‘Cinta Yang Agung’ Karya Kahlil Gibran - Cici Sulista; Abdul Latif (Institut Agama Islam Negeri Metro, 2020)
The object of this study are two poems from different authors, namely the poem “I Love You In Silence” by Jalaluddin Rumi with the poem “Great Love” by Kahlil Gibran. This study aims to compare the style of language of the two poems. The method used by the authours in this study is the comparison method. The results showed that there where three similarities and two differences found in the two poems. First, there are there are similarities in the style of language. Secondly, there are similiraties in the style of language based on the structure of sentences, both poems use the name style of repetition language, and not only that the third equation is found in the direct or indirect meaning of meaning because both poems also use the style of personification. As for the difference between the two poems there are two differences. First, it lies in the phrase used in the repetitive language style, if in the poem Rumi uses the phrase ‘I Chose’ while Gibran uses the phrase ‘when’. Second, there is difference in the function of the repetitive language style used, when Rumi uses the repetitive language style to confirm the action taken against the person in love, in contrast to Gibran who uses the repetitive language style to explain the true nature of love. Keyword: Poetry, Love, Silence, Great, Language Style.